The North Korean paradox: regime change anyone? - Katsumata, Hiro (2016)
The issue of Pyongyang’s development of nuclear weapons has alarmed countries in East Asia and raised tension between the United States and North Korea, with the threat of war looming over the peninsula. Since President George W Bush pronounced North Korea to be part of an “axis of evil” with Iraq and Iran, Pyongyang has declared its intention to arm itself with nuclear weapons for its survival and called for a non-agression pact with Washington. The US has pressed for multilateral talks involving first China and later Japan, South Korea and Russia as well. The first round of the six-way talks, held in Beijing in late August, has held out the prospect of a resolution that obviates a military attack on North Korea’s nuclear facilities. This paper assesses the different perspectives of the various countries involved in the North Korean issue; whether they favour a regime change in Pyongyang; and the prospects of the six-way talks.